The Impact of the Work Environment on Employee Job Satisfaction with Motivation as an Intervening Variable of the Garden Office of Pt. Tasma Puja Sei Kuamang Kampar - Husein Husein; Yulizar Baharuddin; Mustafa Kamal; Adi Setiawan; Muhammad Salis (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of the work environment on employee job satisfaction with work motivation as an intervening variable in the Garden Office of PT. Tasma Puja Sei Kuamang Kampar. The phenomenon behind this research is the importance of creating a conducive work environment to increase employee motivation and job satisfaction in supporting the achievement of company goals. The research method used is a quantitative method with a descriptive and causal approach. The population in this study is all employees of the Plantation Office of PT. Tasma Puja Sei Kuamang Kampar. The sampling technique uses saturated sampling, so that the entire population is used as a research sample of 52 employees. The data collection technique was carried out through the distribution of questionnaires. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of the study show that the work environment has a positive and significant effect on employee job satisfaction, the work environment has a positive and significant effect on work motivation, and work motivation has a positive and significant effect on employee job satisfaction. In addition, work motivation has been proven to be able to mediate the influence of the work environment on employee job satisfaction at the Garden Office of PT. Tasma Puja Sei Kuamang Kampar. Based on the results of the study, it can be concluded that the work environment and work motivation are important factors in increasing employee job satisfaction. Therefore, companies need to continue to create a comfortable, safe, and conducive work environment and provide support that can increase employee work motivation